2018
DOI: 10.1111/faf.12339
|View full text |Cite
|
Sign up to set email alerts
|

How commercial fishing effort is managed

Abstract: Wild capture fisheries produce 90 million tonnes of food each year and have the potential to provide sustainable livelihoods for nearly 40 million people around the world (http://www.fao.org/3/a-i5555e.pdf). After decades of overfishing since industrialization, many global fish stocks have recovered, a change brought about through effective management. We provide a synthetic overview of three approaches that managers use to sustain stocks: regulating catch and fishing mortality, regulating effort and regulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 90 publications
1
23
0
1
Order By: Relevance
“…Such dynamics are likely manifested in limited entry fisheries that harvest fast-growing and short-lived species. Owing to the life-history characteristics of the exploited species (e.g., high recruitment variability) and restricted fishing technology, Anderson et al (2018) indicated that these seasonal fisheries experience minimal capital stuffing, and hence rent dissipation compared with other fisheries operating under limited entry licensing. For example, in Australia's prawn and rock lobster fisheries with restricted entry programs, fishing fleets show strong sensitivity to decreasing income per time fishing when biomass declines, as measured by the difference between the realized and potential fishing efforts represented by multiplying the fleet size f times season length t (Smith and McKelvey, 1986;Walters and Martell, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such dynamics are likely manifested in limited entry fisheries that harvest fast-growing and short-lived species. Owing to the life-history characteristics of the exploited species (e.g., high recruitment variability) and restricted fishing technology, Anderson et al (2018) indicated that these seasonal fisheries experience minimal capital stuffing, and hence rent dissipation compared with other fisheries operating under limited entry licensing. For example, in Australia's prawn and rock lobster fisheries with restricted entry programs, fishing fleets show strong sensitivity to decreasing income per time fishing when biomass declines, as measured by the difference between the realized and potential fishing efforts represented by multiplying the fleet size f times season length t (Smith and McKelvey, 1986;Walters and Martell, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Notable examples are British Columbia and Bristol Bay salmon fisheries, where in the latter example vessel owners compete to situate their nets nearest to the river mouth (Walters, 1998;Anderson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…By limiting and authorizing the free exchange of licences and adopting catch share programmes, a fisheries management system transitions away from state‐governed allocation to an allocation regime‐grounded private property arrangements and free market principles (Anderson et al, ; Bromley, ; Mansfield, ). Economic efficiency, managerial feasibility and resource conservation are often the stated rationale, while incentivizing payments towards management costs from those that remain is also prioritized.…”
Section: Licences and Licensing Within Fisheries Management Systemsmentioning
confidence: 99%
“…By limiting and authorizing the free exchange of licences and adopting catch share programmes, a fisheries management system transitions away from state-governed allocation to an allocation regime-grounded private property arrangements and free market principles (Anderson et al, 2019;Bromley, 2008;Mansfield, 2004).…”
Section: Cen Ce S and LI Cen S Ing Within Fis Herie S Manag Emenmentioning
confidence: 99%
“…fisheries | human mobility | movement ecology | natural resource management | resilience B etter understanding of human behavior is now an important component of the natural-resource management toolbox (1). The big data revolution that is taking place across multiple social systems and scales holds great promise for incorporating human behavioral data into management.…”
mentioning
confidence: 99%